The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1119/10.0003662
|View full text |Cite
|
Sign up to set email alerts
|

Resources for Supporting Students With and Without Disabilities in Your Physics Courses

Abstract: All students deserve access to effective, equitable physics education. Postsecondary faculty have been shown to be unprepared to support students with disabilities in their classes, and popular, research-based introductory physics curricula do not adequately plan for variations in learners’ needs, abilities, and interests. It is urgent to address this disparity because students with disabilities are enrolling in postsecondary education at increasing rates and enroll in STEM degree programs at steady rates. Spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Even with the sizeable representation of disabled students in postsecondary STEM, research has shown that popular, research-based curricular materials are not designed with learner variation in mind [9]. There are also barriers in the structure of STEM courses, for example, distracting room layouts in SCALE-UP courses and lack of access to course materials outside of class [10][11][12]. Additionally, STEM faculty on average hold more negative beliefs about disability than their peers in other academic disciplines [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Even with the sizeable representation of disabled students in postsecondary STEM, research has shown that popular, research-based curricular materials are not designed with learner variation in mind [9]. There are also barriers in the structure of STEM courses, for example, distracting room layouts in SCALE-UP courses and lack of access to course materials outside of class [10][11][12]. Additionally, STEM faculty on average hold more negative beliefs about disability than their peers in other academic disciplines [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%